Study on the construction of historical toponymic information management system for Essence of the Geographical Content of the History Books. Issue 4 (2nd October 2017) - Liu, Longyu; Hu, Di
ABSTRACT: Over the last decades, to promote the study of historical geography, a number of institutions have constructed historical GIS platforms. Correspondingly, a large number of historical studies require more detailed information on historical toponyms, and there is an urgent need for improving and expanding the toponymic information on the existing historical GIS platforms. Therefore, in this paper, we selected Du Shi Fang Yu Ji Yao, one of the most representative books of historical geography, as the data source. We analyzed the geographic information in the book, especially the structure and characteristics of the toponymic information, according to the particularities of administrative regions in the Ming Dynasty, and designed a spatio-temporal data model for both administrative and non-administrative region toponyms. The both types of toponyms are used to construct an information database on more than 60, 000 toponyms in Essence of the Geographical Content of the History Books that provides a convenient destination for inquiries by containing more abundant and precise toponymic information of the Ming Dynasty, and develop a toponymic information management system of the Essence of the Geographical Content of the History Books, in which the toponymys can be rapidly extracted, separated and used to establish relationships between them.